2018
DOI: 10.1021/acsnano.8b03414
|View full text |Cite
|
Sign up to set email alerts
|

Fermi Level Manipulation through Native Doping in the Topological Insulator Bi2Se3

Abstract: The topologically protected surface states of three-dimensional (3D) topological insulators have the potential to be transformative for high-performance logic and memory devices by exploiting their specific properties such as spin-polarized current transport and defect tolerance due to suppressed backscattering. However, topological insulator based devices have been underwhelming to date primarily due to the presence of parasitic issues. An important example is the challenge of suppressing bulk conduction in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 44 publications
(73 reference statements)
2
37
0
Order By: Relevance
“…We will henceforth refer to vacancies in the surface (bulk) QL with a subscript 's'('b'). An Se vacancy in a 6×6×6 QLs slab corresponds to a defect concentration of ≈ 10 19 cm −3 (in-plane concentration = 2.6 × 10 13 cm −2 ), comparable to the values reported in experiments, 15,22 which range from 10 11 to 10 20 cm −3 . Additional details of charge-states of the VSe defects and their stability under different conditions are given in the Supplement (S4).…”
supporting
confidence: 83%
“…We will henceforth refer to vacancies in the surface (bulk) QL with a subscript 's'('b'). An Se vacancy in a 6×6×6 QLs slab corresponds to a defect concentration of ≈ 10 19 cm −3 (in-plane concentration = 2.6 × 10 13 cm −2 ), comparable to the values reported in experiments, 15,22 which range from 10 11 to 10 20 cm −3 . Additional details of charge-states of the VSe defects and their stability under different conditions are given in the Supplement (S4).…”
supporting
confidence: 83%
“…However, sometimes the position of the Fermi level cannot be properly tuned only by using electrical gating to the same or the adjacent regime to the intrinsic Fermi level, because it might fall into the valence band under negative voltages. Elemental doping has been confirmed to be an effective approach to assist the manipulation of Fermi level in topological insulator nanostructures [42][43][44]. In 2012, Wang et al reported the Na elemental doping in Bi 2 Te 3 nanoplates synthesized by solvothermal method [45].…”
Section: Field-effect Transistormentioning
confidence: 99%
“…Therefore, high quality p-type crystals are critically important for basic as well as applied research on Bi 2 Se 3 , and a great deal of research work has been devoted to manipulating the Fermi level by searching for suitable p-type dopants. These efforts include volumetric doping with elements, such as Mn [ 10 ], Sn [ 4 ], Fe [ 11 , 12 ], Ca [ 13 , 14 ], Mg [ 15 ], Cr [ 16 , 17 ], Pb [ 18 ], surface adsorption with Fe [ 19 , 20 ], Co [ 21 ], and controlling a number of native anti-site defects [ 22 , 23 , 24 ]. Doping with magnetic materials is particularly important due to the fact that the magnetic order leads to the breaking of the time reversal symmetry, and thus, can destroy the topological order.…”
Section: Introductionmentioning
confidence: 99%